Pengaruh Jumlah Penduduk, Produk Domestik Regional Bruto Dan Belanja Daerah Terhadap Penerimaan Pajak Daerah Pada Kabupaten/Kota Di Provinsi Sumatera Utara - Saniah, Rizqan; Murtala, Murtala (LPPM UNIMAL, 2023)
This study aims to determine the effect of Population, Gross Regional Domestic Product, and Regional Expenditure on Regional Tax Revenue in 12 Regencies/Cities in North Sumatra Province in 2012-2021. The data used in this research is data obtained from the Central Bureau of Statistics. The analytical method used is panel data regression using the E-views 10 program. The results show that partially the population variable has a negative and significant effect on local tax revenues, the Gross Regional Domestic Product (GRDP) variable has a significant and significant effect on local tax revenues, and variables Regional spending has an effect on and is significant on local tax revenues. The results of the study simultaneously the variables of population, GRDP, and regional expenditure have an effectsignificant to the local tax revenue variable. Coefficient of Determination ( ) of 0.624721 which means that the effect of population, GRDP and regional spending on regional tax revenues is 0.624721 or 62.47% while the remaining 37.53% influenced by variables outside this study.